ETUDE ANATOMIQUE DES VEINES CEREBRALES SUPERIEURES - Piffer, C. R.; Horn, Y.; Hureau, J.; Meininger, V. (My University, 1985)
The authors describe the number, courses, fixations and dispositions of the superior cerebral veins at the levels of the subdural space and of the superior sagittal sinus. It was observed that the superior cerebral veins have different courses to the superior sagittal sinus, and that these vascular walls are fixed to the interne face of the cranial dura-mater and to the lateral wall of the sinus. Frequently, the wall of the posterior vein adheres to the falx cerebri, presenting ascendant traject to the inferior wall of the sinus. It was noted that the anterior veins open into the superolateral angle of the superior sagittal sinus, forming an acute forwards and right angle with it; the middle veins open near to the inferior angle of the sinus, with which they form an acute forwards or a right angle; the posterior veins enter the inferior angle of the sinus, forming an acute forwards angle with it. The authors confirm the superior cerebral veins draining into the superior sagittal sinus in sense favorable the current of the blood within it.
The anatomical observations of the superior cerebral veins